Pengembangan Multimedia Interaktif Materi Cuaca untuk Kelas 3 Sekolah Dasar - Ngananti, Anggun Citra Putri; Basuki, Imam Agus; Rahayuningtyas, Wida (University of Muhammadiyah Malang, 2023)
Technology provides changes in the application of student learning, which initially could only listen to explanations from teachers and understand material that only comes from textbooks. Still, with current technological developments, the information obtained is sourced from student books and interactive media. This research aims to produce interactive multimedia weather material for class 3 SDN Bareng 2 Malang and to analyze the validity, attractiveness, and effectiveness of class 3 SDN Bareng 2 Malang. This development research uses the ADDIE model to measure validity, effectiveness, and attractiveness later—interactive multimedia on whether the material was developed for grade 3 at the elementary school level. The results of the validity of multimedia obtained from material experts amounted to 93.75% and entered the criteria for a very valid eligibility level. Meanwhile, media experts are 88.3% in the very valid category. Then, the results of linguists are 90% and reach the criteria of very valid or appropriate to be used as learning media and can be tested in the field. Then, the results of the attractiveness of multimedia obtained 98.9% with desirable criteria. The effectiveness of getting a score from the pre-test in individual trials reached a score of 140. In the post-test, it achieved a score of 250. Furthermore, small group trials achieved 870 in the pre-test results. Then, the post-test results rose to 1350. The final test was the field trial to 2365, and then the post-test score increased to 3965. In conclusion, the pre-test and post-test scores increased from 62 students in grade 3 at SDN Bareng 2, which was 54.43% in the pre-test then 89.75% in the post-test.